Monocyte Adhesion and Spreading on Human Endothelial Cells Is Dependent on Rho-regulated Receptor Clustering - Wójciak-Stothard, Beata (The Rockefeller University Press, 1999)
The GTPase Rho is known to mediate the assembly of integrin-containing focal adhesions and actin stress fibers. Here, we investigate the role of Rho in regulating the distribution of the monocyte-binding receptors E-selectin, ICAM-1, and VCAM-1 in human endothelial cells. Inhibition of Rho activity with C3 transferase or N19RhoA, a dominant negative RhoA mutant, reduced the adhesion of monocytes to activated endothelial cells and inhibited their spreading. Similar effects were observed after pretreatment of endothelial cells with cytochalasin D. In contrast, dominant negative Rac and Cdc42 proteins did not affect monocyte adhesion or spreading. C3 transferase and cytochalasin D did not alter the expression levels of monocyte-binding receptors on endothelial cells, but did inhibit clustering of E-selectin, ICAM-1, and VCAM-1 on the cell surface induced by monocyte adhesion or cross-linking antibodies. Similarly, N19RhoA inhibited receptor clustering. Monocyte adhesion and receptor cross-linking induced stress fiber assembly, and inhibitors of myosin light chain kinase prevented this response but did not affect receptor clustering. Finally, receptor clusters colocalized with ezrin/moesin/ radixin proteins. These results suggest that Rho is required in endothelial cells for the assembly of stable adhesions with monocytes via the clustering of monocyte-binding receptors and their association with the actin cytoskeleton, independent of stress fiber formation.